Guerrilla warfare and the dynamics of violence in the Irish War of Independence - TORMEY, THOMAS (Trinity College Dublin. School of Histories & Humanities. Discipline of History, 2020)
Drawing on a long tradition of area studies on irregular warfare and county studies in Irish history, this thesis examines the Irish War of Independence in the counties of Dublin and Roscommon. The thesis centres on the analysis of the significance, execution, occurrence, authorship, and consequences of the small actions that it holds to form the core element of the conflict as both a political contest for power and a lived experience. In order to do this, the thesis offers a treatment of both the dynamics of the conflict itself and the nature of individual activism in both an urban and rural setting. The central importance of cover for guerrilla units, regardless of geographical milieu, will be highlighted. The idea of cover, in its broadest sense, taken to mean an ability to avoid both detection and fire, had different manifestations in different environments: the city offered anonymity, the countryside offered privacy. The treatment draws on a broadly based historical methodology that includes aspects of diplomatic, political, and strategic histories-from-above, as well as tactical military, political, and social histories-from-below
APPROVED